2012
DOI: 10.3109/10799893.2012.738689
|View full text |Cite
|
Sign up to set email alerts
|

Loss of lysophosphatidic acid receptor-3 suppresses cell migration activity of human sarcoma cells

Abstract: Lysophosphatidic acid (LPA) interacts with at least six G protein-coupled transmembrane LPA receptors (LPA(1)-LPA(6)). Recently, we have reported that LPA(3) indicated opposite effects on cell migration, depending on the cell types. In the present study, to assess an involvement of LPA(3) on cell migration of sarcoma cells, we generated LPA receptor-3 (LPAR3)-knockdown (HT1080-sh3 and HOS-sh3, respectively) cells from fibrosarcoma HT1080 and osteosarcoma HOS cells, and measured their cell migration abilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Although LPA treatment could stimulate LPAR1–3 and their downstream G proteins, Gα i and Gα q coupled with LPAR1/3 were closely involved in the LPA‐induced hMSC migration. Interestingly, it has been reported that LPAR1–3 have different functions in cell motility regulation , suggesting that LPA exerts different responses in the distribution and expression levels of the LPAR receptors and their downstream signals depending on the specific cell type. Previous studies have shown that the activation of Gα q or Gβγ i results in the stimulation of phospholipase C activity, leading to phosphatidylinositol‐(4,5)‐bisphosphate hydrolysis and Ca 2+ mobilization from internal stores, and the subsequent activation of protein kinase C (PKC) .…”
Section: Discussionmentioning
confidence: 99%
“…Although LPA treatment could stimulate LPAR1–3 and their downstream G proteins, Gα i and Gα q coupled with LPAR1/3 were closely involved in the LPA‐induced hMSC migration. Interestingly, it has been reported that LPAR1–3 have different functions in cell motility regulation , suggesting that LPA exerts different responses in the distribution and expression levels of the LPAR receptors and their downstream signals depending on the specific cell type. Previous studies have shown that the activation of Gα q or Gβγ i results in the stimulation of phospholipase C activity, leading to phosphatidylinositol‐(4,5)‐bisphosphate hydrolysis and Ca 2+ mobilization from internal stores, and the subsequent activation of protein kinase C (PKC) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the LPA/LPAR3 signaling may initiate mutation-independent epithelial-to-mesenchymal transition (EMT) through β1-integrin-dependent activation of Wnt/β-catenin signaling [ 60 ]. Pharmacological suppression of LPAR3 would suppress motility and invasion in various cancers, including hamster pancreatic cancer cells [ 61 ], human triple-negative breast cancers [ 62 ], fibrosarcoma HT1080 cells, and osteosarcoma HOS cells [ 63 ]. Direct targeting of LPAR3 by miR-15b has been shown to repress cell proliferation and drive the senescence and apoptosis of ovarian cancer cells through the PI3K/Akt pathway [ 64 ], suggesting the potential mRNA treatment against LPAR3.…”
Section: Lpa Receptor-mediated Signaling In Cancer Biologymentioning
confidence: 99%
“…This observation suggests that various gastric cancer cells expressed variable levels of LPAR1, LPAR2, and LPAR3 without a consistent pattern (Shida et al, 2004;Yang et al, 2013). LPAR3, in particular, has been shown to be upregulated in a variety of cancer types, including sarcoma, gastric, liver epithelial and pancreatic cancer (Tanabe et al, 2012;Inoue et al, 2013;Kato et al, 2012). The effect of LPA on gastric cancer migration with and without LPAR3 knockdown was then evaluated and the effect of LPA on migration was shown to be blocked in shLPAR3transfected BGC-803 cells.…”
Section: Discussionmentioning
confidence: 99%